2020
DOI: 10.1039/c9an01624d
|View full text |Cite
|
Sign up to set email alerts
|

Tap water fingerprinting using a convolutional neural network built from images of the coffee-ring effect

Abstract: A low-cost tap water fingerprinting technique was evaluated using the coffee-ring effect, a phenomenon by which tap water droplets leave distinguishable "fingerprint" residue patterns after water evaporates. Tap waters from communities across southern Michigan dried on aluminum and photographed with a cell phone camera and 30× loupe produced unique and reproducible images. A convolutional neural network (CNN) model was trained using the images from the Michigan tap waters, and despite the small size of the ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Soil patterns contain significant information which can be utilised and implemented as a component of a multi-sensor instrument once the effect of soil texture and analysis of mixed soils is assessed. The preliminary work of Li et al (91) indicated clear potential for a water quality analysis method that would provide a cheap blanket test for all contaminants instead of just one. To increase the accuracy of this model, a bigger database is needed for CNN training.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Soil patterns contain significant information which can be utilised and implemented as a component of a multi-sensor instrument once the effect of soil texture and analysis of mixed soils is assessed. The preliminary work of Li et al (91) indicated clear potential for a water quality analysis method that would provide a cheap blanket test for all contaminants instead of just one. To increase the accuracy of this model, a bigger database is needed for CNN training.…”
Section: Discussionmentioning
confidence: 99%
“…Water quality analysis is also possible using this method Li et (91), obviating negative effect on human health (92) of contaminated water and improves on tested methods which detect only specific contaminants (91). Tap water samples were collected from across Michigan, each having underwent different water treatments.…”
Section: Fig 20 Dried Drop Crystallisation Patterns Within Drops Of 4...mentioning
confidence: 99%
“…The proposed CNN model with fewer neurons can achieve better suppression of overfitting and robustness to noise. Li et al in [19] present tap water fingerprinting using a convolutional neural network built from images of the coffee-ring effect. These experiments' results suggest that the unique and reproducible residue patterns of tap water samples that can be imaged with a cell phone camera and a loupe contain a wealth of information about the overall composition of the tap water.…”
Section: Related Workmentioning
confidence: 99%
“…In this investigation, we propose using the pattern left by an evaporated drop as a unique signature of each compound, unaltered or not. The analysis of patterns formed by droplet evaporation has already been used in many fields, such as diagnosis of pathologies [9][10][11], bioassays analysis, study of bacteria motility [12][13][14], detection of structural changes in liposomes [15], development of agricultural products [16][17][18], among many others [19][20][21][22][23][24][25]. One of the main objectives of the drop evaporation method is to create, in dried residues of droplets, certain morphological characteristics that may be easily identified and quantified.…”
Section: Introductionmentioning
confidence: 99%